ANALISIS KESULITAN SISWA DALAM PEMBELAJARAN NAHWU DI MA PERSIS BANGIL - Syailendra, Fawwaz; Fauji, Imam (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
One of the sciences used to learn Arabic is nahwu. Through this, one can understand the function and grammatical rules of a word within a sentence. The purpose of nahwu is to prevent errors in pronunciation or writing, particularly in diacritical marks or letters within a sentence, which can lead to a change in meaning. The aim of this study is to identify the factors that cause students at Madrasah Aliyah (MA) PERSIS Bangil to experience difficulties in learning nahwu. This research uses a qualitative method with a descriptive approach. The data was collected through classroom and dormitory observations, interviews with relevant students, and documentation. The findings reveal two main factors contributing to the difficulties. The first is internal factors, such as weak memory related to your lessons and a lack of interest or motivation to study. The second is external factors, including teachers who are less interactive and a learning environment that is not supportive of nahwu instruction